Multisystem Inflammatory Syndrome (MIS-C) in an Adolescent Nigerian Girl with COVID-19: A call for vigilance in Africa - Onyeaghala, Chizaram; Alasia, Datonye; Eyaru, Orezioghene; Nsirim, Paul; Maduka, Omosivie; Osemwegie, Nosa; Ugwueze, Nkem; Ordu, Collins; Igbosi, Ebitei; Irabor, Mary; Eyidia, Emeka (My University, 2020)
Majority of reports of Multisystem Inflammatory Syndrome (MIS-C) associated with COVID-19 have come from Europe and North America, with a paucity of cases in the Asia-Pacific region and Africa. The paucity of reports in Africa is in contrast with the demographics of the series in New York, Paris and UK which reported that children of African ancestry accounted for 40%, 57% and 75%, respectively of all cases of MIS-C. With the global trend of higher prevalence of MIS-C in children of African ancestry, enhanced surveillance and awareness for this syndrome in children with COVID-19 in Africa is therefore important as the previous and current observations of Kawasaki Disease (KD) and MIS-C as a rarity in Africa may be due to under-reporting, a poor index of suspicion and missed diagnosis. A case report of a 12-year old Nigerian girl with MIS-C is presented in line with the WHO call for urgent reporting and global surveillance especially in areas were MIS-C is considered a rarity. This case report stimulates a call for vigilance and expanded effort at surveillance to promote early recognition and diagnosis of MIS-C in Africa; using current case definitions which promote the recognition of MIS-C in areas of resource limitation. The favourable outcome and experience from this case will create awareness, expand knowledge, and support clinicians on the African continent in their approach to other potential cases.
Keywords: Africa; COVID-19; Kawasaki; MIS-C; SARS-CoV-2